The Euro Introduction and Non-Euro Currencies - Dick van Dijk; Haris Munandar; Christian M. Hafner (Tinbergen Institute, 2005)
This paper documents the existence of large structural breaks in the unconditional correlations among the British pound, Norwegian krone, Swedish krona, Swiss franc, and euro exchange rates (against the US dollar) during the period 1994-2003. Using the framework of dynamic conditional correlation (DCC) models, we find that such breaks occurred both at the time the formal decision to proceed with the euro was made in December 1996 and at the time of the actual introduction of the euro in January 1999. In particular, we document that most correlations were substantially lower during the intermittent period. We also find breaks in unconditional volatilities at the same points in time, but these are of a much smaller magnitude comparatively.
Keywords: C32; F31; F36; G15; 330; Exchange rates; multivariate GARCH; dynamic conditional correlation; structural breaks; Euro; Wechselkurs; Pfund Sterling; Französischer Franc; US-Dollar; Währungsumstellung; Strukturbruch; ARCH-Modell; Zeitreihenanalyse